2017
DOI: 10.1080/17441692.2017.1287211
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of debt relief on under five mortality rate in Sub-Saharan Africa

Abstract: This paper examines the impact of the Highly Indebted Poor Countries (HIPC) Initiative on under five mortality rate (U5MR) in Sub-Saharan Africa. The HIPC Initiative involves debt forgiveness and the redirection of funds that were meant to service external debt towards the provision of social services and poverty reduction in eligible countries. The Initiative is akin to a natural experiment since some countries benefited while some did not, and the timing of debt forgiveness varied across countries. We exploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The last two articles in this grouping utilise data from several countries to examine the impact of environmental health hazards (Adjiwanou & Engdaw, 2017) and the impact of debt relief on childhood mortality (Oryema, Picone, & Gyimah-Brempong, 2017). Utilising Demographic and Health Survey data from 12 sub-Saharan African countries, Adjiwanou and Engdaw (2017) conclude that improvement in household environmental conditions can reduce the risk of mortality during late childhood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last two articles in this grouping utilise data from several countries to examine the impact of environmental health hazards (Adjiwanou & Engdaw, 2017) and the impact of debt relief on childhood mortality (Oryema, Picone, & Gyimah-Brempong, 2017). Utilising Demographic and Health Survey data from 12 sub-Saharan African countries, Adjiwanou and Engdaw (2017) conclude that improvement in household environmental conditions can reduce the risk of mortality during late childhood.…”
Section: Introductionmentioning
confidence: 99%
“…The policy implication here is obvious: there is a need to put in place policies and interventions which aim to improve environmental health for better success in reducing childhood mortality in the region. On the other hand, Oryema et al (2017) investigate the impact of highly indebted poor countries initiative (HIPC) and Multilateral Debt Relief Initiative on under-five child mortality rate in sub-Saharan Africa. Their statistically robust study finds that HIPC reduces child mortality and the effects are important.…”
Section: Introductionmentioning
confidence: 99%
“…Mix findings characterized the results of the extant literature on the effect of official development assistance and health outcome (Bendavid & Bhattacharya, 2014;Ebeke & Drabo, 2011;Gupta et al, 2018;Kotsadam et al, 2018;Maju et al, 2019;Mallaye & Yogo, 2012;Ndikumana & Pickbourna, 2016;Negeri & Halemariam, 2016;Oryema et al, 2017;Pitt et al, 2018). One strand of the literature reports that aid improves health outcomes, promoting the argument on the effectiveness of aid in promoting development in the recipient country (Chauvet et al, 2008;Ebeke & Drabo, 2011;Mallaye & Yogo, 2012;Masud & Yontcheva, 2005;Negeri & Halemariam, 2016).…”
Section: Introductionmentioning
confidence: 79%
“…Maju et al (2019) noted that an increase in water and sanitation expenditures occasioned by demand for more and appropriate foreign aid allocation could lead to a reduction in women's exposure to some deadly diseases like HIV/AIDS. Oryema et al (2017) investigated the effect of debt relief on the under-five-mortality rate in SSA and reported that participation in High Indebted Poor Countries Initiative significantly decreases under-5-mortality rate while outright debt cancellation is not statistically significant. Dingle et al (2020), employed Muskoka2 method in estimating the level of aid for reproductive, maternal, newborn and child health for the period of 2002-2017, reported that the proportion of this class of aid received by low-income countries increased from 31% in 2002 to 52% in 2017.…”
Section: Foreign Aid and Health Outcomementioning
confidence: 99%
“…This rate varies depending on exemption options for different commodities or services (Mawejje & Munyambonera, 2016). Such persistently high taxes that seem not to be commensurate with service delivery have stimulated a raging debate among the international development partners, between those fronting tax cuts versus debt forgiveness as a solution to the low levels of growth and poverty ravaging most of the low-income countries (LIC) (Pohwani et al, 2019), this debate continues to date even though rich countries have in the past written off debts to poor countries but to avail (Oryema et al, 2017). Some of the tax rates in Uganda are among the highest in the world.…”
Section: Introductionmentioning
confidence: 99%